Hyperglycemia induces abnormal gene expression in hematopoietic stem cells and their progeny in diabetic neuropathy - Katagi, Miwako (2014)
Diabetic peripheral neuropathy is a major chronic diabetic complication. We have previously shown that in type 1 diabetic streptozotocin-treated mice, insulin- and TNF-α co-expressing bone marrow-derived cells (BMDCs) induced by hyperglycemia travel to nerve tissues where they fuse with nerve cells, causing premature apoptosis and nerve dysfunction. Here we show that similar BMDCs also occur in type 2 diabetic high-fat diet (HFD) mice. Furthermore, we found that hyperglycemia induces the co-expression of insulin and TNF-α in c-kit(+)Sca-1(+)lineage(+) (KSL) progenitor cells, which maintain the same expression pattern in the progeny, which in turn participates in the fusion with neurons when transferred to normoglycemic animals.